Outpatient Educational Environment of Dental Medical Colleges of Bangladesh Utilizing Acleem Questionnaire - Mainul Haque (Journal of Global Pharma Technology, 2017)
Background: The learning environment as: ‘a social system that includes the learner (including the external relationships and other factors affecting the learner), the individuals with whom the learner interacts, the setting(s) and purpose(s) of the interaction, and the formal and informal rules/policies/norms governing the interaction’ [2]. Educational environment both academic and clinical, are substantial elements carrying out medical students’ attitudes, knowledge, skills, progression, behaviors and achievements Methods: This was a cross sectional study. The study participants were Dental students of Dhaka Dental College and Mandy Dental College, Dhaka, Bangladesh. Data were collected in early 2017. The universal sampling method was adopted. ACLEEM validated instrument was utilized for the data collection. Data were using SPSS Version 21. Results: The response rate was 100%. The total study population was 134. Among the current SP 32.8% (44) and 67.2% (90) were male and female respectively. The reliability and Validity of the Questionnaire regarding local context were Cronbach’s alpha 0.939 and convergent validity -0.013-0.682 There were no statistically significant (p>0.05) differences observed between sex and dental colleges in the domain of Clinical Teaching, Clinical Training and Total when analyzed with an independent t-test. Conclusions: The ACLEEM instrument was valid and reliable to measure ambulatory educational environment for Bangladeshi for Dental School. Most of the study participants had positive perception regarding their education environment.Keywords: Acleem, Dental colleges, Bangladesh.